1984
DOI: 10.1152/ajpgi.1984.247.1.g37
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of motility changes during acute intestinal obstruction in the dog

Abstract: We investigated the effects of autonomic drugs and the role of intestinal contents on the motility changes that occur during acute obstruction. Myoelectric activity was recorded from seven electrodes spaced at 3-cm intervals along the midjejunum of nine conscious dogs. Another animal had electrodes evenly placed throughout the small bowel. Obstruction was created by inflation of an intraluminal balloon. Systemic arterial blood pressure and pulse rate were monitored. Initially, motor activity of the small intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…tumors and diverticulitis. In laboratory animals, lumen dilation has been reproduced by external application of a silicon band [7-9], or by inflation of an intraluminal balloon [6, 35]. In the present study, we found that no matter the method, lumen dilation leads to gene expression of COX-2 in the alimentary tract.…”
Section: Discussionsupporting
confidence: 58%
“…tumors and diverticulitis. In laboratory animals, lumen dilation has been reproduced by external application of a silicon band [7-9], or by inflation of an intraluminal balloon [6, 35]. In the present study, we found that no matter the method, lumen dilation leads to gene expression of COX-2 in the alimentary tract.…”
Section: Discussionsupporting
confidence: 58%
“…Bowel obstruction leads to altered motility function with suppression in smooth muscle contractility (5,43,53). Motility dysfunction is responsible for symptoms such as vomiting, abdominal distension, pain, and constipation (34,46), and may lead to intestinal failure (13,47). The molecular mechanisms underlying these changes are not known.…”
mentioning
confidence: 99%
“…Seven segments were of terminal ileum resected at the time of a right hemicolectomy performed for tumours (5) or ulcerative colitis (2); five were macroscopically healthy looking areas of gut located between stenoses in patients with Crohn's disease. The loops were 5 to 8 cm long and in them we assessed a 1 cm long stenosis perfused with normal saline.…”
mentioning
confidence: 99%